Predicting ablation zones with multislice volumetric 2-D magnetic resonance thermal imaging. (1st January 2021) - Campwala, Zahabiya; Szewczyk, Benjamin; Maietta, Teresa; Trowbridge, Rachel; Tarasek, Matthew; Bhushan, Chitresh; Fiveland, Eric; Ghoshal, Goutam; Heffter, Tamas; Gandomi, Katie; Carvalho, Paulo Alberto; Nycz, Christopher; et al.
Abstract: Background: High-intensity focused ultrasound (HIFU) serves as a noninvasive stereotactic system for the ablation of brain metastases; however, treatments are limited to simple geometries and energy delivery is limited by the high acoustic attenuation of the calvarium. Minimally-invasive magnetic resonance-guided robotically-assisted (MRgRA) needle-based therapeutic ultrasound (NBTU) using multislice volumetric 2-D magnetic resonance thermal imaging (MRTI) overcomes these limitations and has potential to produce less collateral tissue damage than current methods. Objective: To correlate multislice volumetric 2-D MRTI volumes with histologically confirmed regions of tissue damage in MRgRA NBTU. Methods: Seven swine underwent a total of 8 frontal MRgRA NBTU lesions. MRTI ablation volumes were compared to histologic tissue damage on brain sections stained with 2, 3, 5-triphenyltetrazolium chloride (TTC). Bland-Altman analyses and correlation trends were used to compare MRTI and TTC ablation volumes. Results: Data from the initial and third swine's ablations were excluded due to sub-optimal tissue staining. For the remaining ablations ( n  = 6), the limits of agreement between the MRTI and histologic volumes ranged from −0.149 cm 3 to 0.252 cm 3 with a mean difference of 0.052 ± 0.042 cm 3 (11.1%). There was a high correlation between the MRTI and histology volumes ( r 2 = 0.831) with a strong linear relationship ( r  = 0.868). Conclusion: We used a volumetric MRTI technique to accurately track thermal changes during MRgRA NBTU in preparation for human trials. Improved volumetric coverage with MRTI enhanced our delivery of therapy and has far-reaching implications for focused ultrasound in the broader clinical setting.